After Reagan : Bush, Dukakis, and the 1988 election - Pitney, John J., Jr., 1955- (American presidential elections., 2019)
"The story of the 1988 presidential election often revolves around pivotal moments in the campaigns, such as the perceived blunders of Gov. Michael Dukakis of Massachusetts and the famous line by George H. W. Bush: "Read my lips: no new taxes." The election was seen at the time as fairly close, especially in comparison to Reagan's overwhelming landslide victory in 1984. But Bush defeated Dukakis with 426 electoral votes and 53.4 percent of the popular vote, a win larger than Barack Obama's in 2008. In hindsight, the 1988 election was not only a dominant win for Bush but a turning point towards the post-Cold War, hyperpartisan, culturally divided politics that have characterized presidential elections ever since. What stands out in retrospect is how different the world was during 1988 election. Both campaigns were funded from the federal treasury. Republicans seemed to have a lock on the presidency while Democrats controlled Congress. The electorate was more white and less educated than in subsequent years. And no one realized the Berlin Wall would fall the next year, along with the Soviet Union two years later, and usher in a new era of globalization. After Reagan chronicles the events of the 1988 election and shows that, despite what the pundits perceived at the time, the election ultimately rested on the larger social and political context. Bush's victory existed in the afterglow of Reagan's popularity and depended on social dynamics that were thrown into upheaval in the following years. By looking at the election in a fresh light, John J. Pitney Jr. reveals how much we can learn about our current political situation"--